2011
DOI: 10.1007/s00122-011-1652-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular mapping of two QTLs with major effects for resistance to Fusarium head blight in wheat

Abstract: Fusarium head blight (FHB) is a devastating disease of wheat worldwide. Novel sources of resistance are critical for improving FHB resistance levels in wheat. From a large-scale evaluation of germplasm for reactions to FHB, we identified one wheat accession (PI 277012) that consistently showed a high level of resistance in both greenhouse and field experiments. To characterize the FHB resistance in this accession, we developed a doubled haploid (DH) mapping population consisting of 130 lines from the cross bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 40 publications
5
54
0
Order By: Relevance
“…A possible reason is that different Q alleles are present in durum vs. common wheat, which was supported by results of Jantasuriyarat et al [ 51 ] and Faris [ 50 ]. Like in Buerstmayr et al [ 21 ], this locus also contributed to spike compactness in the current study, explaining 23% phenotypic variation (data no shown); but it was not associated with strong FHB resistance as in Buerstmayr et al [ 21 ], Chu et al [ 52 ], and Zhang et al [ 53 ].…”
Section: Discussionsupporting
confidence: 71%
“…A possible reason is that different Q alleles are present in durum vs. common wheat, which was supported by results of Jantasuriyarat et al [ 51 ] and Faris [ 50 ]. Like in Buerstmayr et al [ 21 ], this locus also contributed to spike compactness in the current study, explaining 23% phenotypic variation (data no shown); but it was not associated with strong FHB resistance as in Buerstmayr et al [ 21 ], Chu et al [ 52 ], and Zhang et al [ 53 ].…”
Section: Discussionsupporting
confidence: 71%
“…Some effective FHB resistance sources have been identified in common wheat (Chu et al 2011), and some FHB resistance quantitative trait loci (QTLs) have also been found and mapped in wheat relatives (Cai et al 2005;Chen et al 2007). In recent years, some geneticists and breeders have paid much ata These authors contributed equally to this work.…”
Section: Abstract: Agronomic Trait; Fhb; Resistance Evaluation; Tritimentioning
confidence: 99%
“…At present, there is still no economic and effective way to control this disease. Developing resistant cultivars is an important approach to control this disease, for which the decisive step is to identify new germplasm with multi-resistance.Some effective FHB resistance sources have been identified in common wheat (Chu et al 2011), and some FHB resistance quantitative trait loci (QTLs) have also been found and mapped in wheat relatives (Cai et al 2005;Chen et al 2007). In recent years, some geneticists and breeders have paid much ata These authors contributed equally to this work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol has been successfully used to develop mapping populations and adapted germplasm in our wheat germplasm enhancement programme and durum wheat breeding programme (Chu et al. ,b, , ,b, ,b, Gu et al. ).…”
Section: Outlines Of a Highly Efficient Approach To Develop Dhs In Whmentioning
confidence: 99%